2015 IEEE International Conference on Multimedia &Amp; Expo Workshops (ICMEW) 2015
DOI: 10.1109/icmew.2015.7169770
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised fusion for forgery localization exploiting background information

Abstract: When image authenticity verification has to be carried out without any knowledge about the possible processing undergone by the image under analysis, it is fundamental to rely on a multi-clue approach, that merges the information stemming from several complementary forensic tools. This paper introduces a fully automatic framework for fusing the maps created by a set of unsupervised forgery localization algorithms, indicating possible manipulated areas. The framework takes into account the forgery maps, their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In fact, to attribute the correct importance to a detector score, one should take into account its overall reliability, the level of confidence associated with the specific decision and its compatibility with other detectors. Experiments in [250], [251] show that the DST approach, with reasonable fusion rules, outperforms consistently all individual tools and also abstract-level fusion, thanks to the use of richer information. It even outperforms machine-learning fusion in the absence of a training set well-aligned with the test set, a recurrent situation in multimedia forensics.…”
Section: Fusionmentioning
confidence: 93%
See 1 more Smart Citation
“…In fact, to attribute the correct importance to a detector score, one should take into account its overall reliability, the level of confidence associated with the specific decision and its compatibility with other detectors. Experiments in [250], [251] show that the DST approach, with reasonable fusion rules, outperforms consistently all individual tools and also abstract-level fusion, thanks to the use of richer information. It even outperforms machine-learning fusion in the absence of a training set well-aligned with the test set, a recurrent situation in multimedia forensics.…”
Section: Fusionmentioning
confidence: 93%
“…Their results clearly show that detectors based on fusion dominate all individual base detectors in terms of accuracy, and the gain is more significant when operating at the abstract level. In [250], [251] fusion is addressed in a more systematic way, relying on the Dempster-Shafer theory (DST) of evidence [252] to meaningfully combine multiple tools at the measurement level. The DST provides a methodology to include concepts like uncertainty, reliability, and compatibility in the decision process.…”
Section: Fusionmentioning
confidence: 99%
“…Research has shown that many editing operations, such as resizing [2] or contrast enhancement [3], will leave unique traces behind. Many forensic algorithms have been developed to detect or identify editing operations [4][5][6][7][8][9][10][11][12][13][14][15]. In recent years, convolutional neural networks (CNNs) have been widely used by researchers to perform forensic tasks such as image tampering detection [9,[16][17][18] and source identification [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…There has been accordingly an increasing research in forgery image localization [1], [2], [3], [4], [8], [9], [10], [16], [17]. The general idea in forgery image detection is to find the local inconsistencies which is caused by the presence of traces left during tampering processes in the investigated image.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed an energy-minimization approach using Markov Random Field to model the prior knowledge about the tampering maps. In [16], [17] the authors proposed a decision fusion framework for the image forensics scenario based on Dempster-Shafer Theory (DST) avoiding the necessity of assigning prior probabilities which would be difficult to estimate. However these methods only considered JPEG compression artifacts.…”
Section: Introductionmentioning
confidence: 99%